Pengaruh Penerapan Model Pembelajaran Kooperatif Teknik Two Stay Two Stray Terhadap Pemahaman Konsep Matematis Siswa Kelas VIII SMPN 1 Kecamatan Pangkalan Koto Baru Kabupaten 50 Kota - Angggraini, Erwina; Haryono, Yulia; Edriati, Sofia (Pendidikan Matematika, 2014)
ABSTRACTÂ Â This research is motivated by the lack of understanding mathematical concepts class VIII SMPN 1 Kecamatan Pangkalan Koto Baru. Because learning is still centered on the teachers and students still lack understanding of concepts in mathematics . One method used to overcome this problem by applying the technique of cooperative learning model two stay two stray in learning . The aims of this researchÂ  is to know the studentâs understanding of mathematical concepts with the implementation of cooperative learning model two stay two stray technique better than studentâs understanding of the mathematical concepts using conventional learning in class VIII SMPN1 Kecamatan Pangkalan Koto Baru academic year 2013/2014 . This research is an experimental study , with a random design on the subject . The population in this research was students of class VIII SMP SMP 1 Kecamatan Koto Baru academic year 2013/20143 . The samples in this reseacrh is randomly technique . Selected VIII.1 as experimental class and VIII.2 as control class. Instrument in this study is the final test in the form of essays . Data were analyzed using the normality test, homogeneity test and t test . Hypothesis test using t-test of the party with the help of software MINITAB , obtained P -value of 0.003 is less than Î± = 0.05 , so it can be concluded that the students understanding of mathematical concepts by implementing cooperative learning model two stay two stray technique is better than studentâs understanding mathematical conceptsÂ  with conventional learning in class VIII SMPN1 Kecamatan Pangkalan Koto Baru the level of 95 %. Â